Consensus Conference on Clinical Management of pediatric Atopic Dermatitis. - Galli, Elena; Neri, Iria; Ricci, Giampaolo; Baldo, Ermanno; Barone, Maurizio; Belloni Fortina, Anna; Bernardini, Roberto; Berti, Irene; Caffarelli, Carlo; Calamelli, Elisabetta; Capra, Lucetta; Carello, Rossella; et al. (Ital J Pediatr, 2016)
The Italian Consensus Conference on clinical management of atopic dermatitis in children reflects the best and most recent scientific evidence, with the aim to provide specialists with a useful tool for managing this common, but complex clinical condition. Thanks to the contribution of experts in the field and members of the Italian Society of Pediatric Allergology and Immunology (SIAIP) and the Italian Society of Pediatric Dermatology (SIDerP), this Consensus statement integrates the basic principles of the most recent guidelines for the management of atopic dermatitis to facilitate a practical approach to the disease. The therapeutical approach should be adapted to the clinical severity and requires a tailored strategy to ensure good compliance by children and their parents. In this Consensus, levels and models of intervention are also enriched by the Italian experience to facilitate a practical approach to the disease.